الدور الاجتماعي للزوايا في وادي سوف خلال فترة الاحتلال 1830 -1962 م - سعود منى; سعود السعدية (جامعة الوادي University of eloued, 2018)
كانت وادي سوف من أوائـل المناطق بالجزائر التي عرفت الزوايا وقد كانت زوايا الطرق الصوفية هي النوع الذي عرفته المنطقة، أين أنارت هـذه الطرق وزواياها فترات حـــــــــالكة من تــــاريخ الأمة الجزائرية، وحياة الناس بالتّعليم القـــــرآني والإرشاد الديني وإصلاح ذات البين، كما كانت دروعا واقيــــة حـافظت على أخلاق وقيـــــــم مجتمعاتنا في عقود تعرضت فيها شعوبنا إلى غزو ثقافي ومسخ حضاري رهيب. هذا ماجعل فالزوايا والطرق الصوفية بوادي سوف تحضى بمكانة هامة، كانت سببا لتشييد الزّوايا في مختلف قرى ومداشر منطقة سوف، حيث كانت محجا لمريدي هذه الطّرق وزواياها، وكانت قلوبهم متشوقة لشيوخها المؤسسين لها،فنظمت الزّيارات وحملت الهدايا والتّبرعات، تأكيدا لمحبتهم وانتمائهم الصّوفي والولاء والطّاعة لشيوخ هذه الزّوايا، ونستطيع القول أنّ هذه الزّوايا قد كان لها الأثر الواضح و الجلي في الحياة الاجتماعية بوادي سوف الذي من خلال التّكافل الاجتماعي وحضورها في الحياة الأسرية و الصحية ، ومساهمتها في الحياة العامة. وغيرها من المهام، بهذه الأفعال والمساهمة تكون الزّوايا قد أدت رسالة جليلة للمجتمع السّوفي حيث كانت قريبة منه في شتى مجالات حياته وخاصة الأسرية منها، بما قدمته له من خدمات و احتضان لتحسسه بالحماية والرعاية التي كفلها حديث رسول الله صلى الله عليه وسلم والذي قال: فيه " مثل المؤمنين في توادهم وتراحمهم كمثل الجسد الواحد إذا اشتكى منه عضو تداعى له سائر الجسد بالسهر والحمى" فكانت الزّوايا هي المؤسسة التي تتداعى لأجل تقديم يد العون والمساعدة للفرد مهما كان جنسه أو معتقده أو توجهه أو قدرته لأن فعلها مرتبط بما خلقت من أجله، فالزّوايا والطّريقة الصّوفية بوادي سوف قد قامت بدور اجتماعي بارز تجلى في عدّة وظائف مارستها وكانت سبب في تفاعلها مع المجتمع، ورسمت من خلالها الزوايا نفوذا داخليا انشأ لها مسؤوليات دينية ودنيوية، فعملت على دعم التّكافل الاجتماعي بين أفراد المجتمع وحققت ما كان يدعوا له الإسلام من أخوة بين المسلمين، وتلبية حاجيات المجتمع فالأسس والمبادئ التي نشأت عليها الزّوايا منذ ظهورها ظلت راسخة رغم تعاقب الأزمان عليها حيث كانت مركزا للإطعام وإيواء طلبة العلم وعابري السّبيل، فهي احتوت المجتمع بمختلف فئاته عندما كان يعانى الأزمات المتوالية، وحافظت على تقاليده وعاداته وأصالته بمواجهة السّياسة الاستعمارية الرّامية إلى طمس معالم المجتمع العربي المسلم به. Wadi Suf was one of the first regions of Algeria to know the corners. The corners of the Sufi roads were the type that the region knew, where these roads and their angles illuminated the dark periods of the history of the Algerian nation, the life of the people in Quranic teaching and religious guidance, And the values of our societies in decades in which our peoples have been subjected to a cultural invasion and a terrible cultural disgrace. This is the source of the Zawiya and the Sufi roads in Wadi. It will have an important place, which was the reason for the construction of the angles in the various villages and districts of Suf, where they were a shrine to the followers of these roads and their angles. Their hearts were eager for their founding sheikhs. These angles, and we can say that these angles have had a clear and visible impact on social life in Wadi Saif through social solidarity and its presence in family life and health, and its contribution to public life. And other tasks, these acts and contribution angles have led to a great message to the community of the Soviet, where it was close to him in various areas of his life, especially family, including the services provided and embrace the sensitivity of protection and care ensured by the Messenger of Allah peace be upon him, which said: "The faithful are like those in the prayer and the mercy of one body, if a member complained to him that the rest of the body fell on him with fever and fever." The corners were the institution that collapses in order to lend a helping hand to the individual, whatever his gender, belief, direction, or ability because he is connected to what he was created for. The mystical way b Wadi Suf has played a prominent social role manifested in several of its functions and was the reason for its interaction with society, and drew through the angles of influence internally established religious and secular responsibilities, and worked to support social solidarity among members of society and achieved what he called Islam of brotherhood among Muslims, And to meet the needs of society, the foundations and principles that have emerged on the angles since its emergence has remained entrenched despite the succession of times as it was a center for feeding and housing students of science and passersby, it included the various groups of society when he was suffering successive crises, and maintained its traditions and customs and originality in the face of POLICY colonial efforts to obliterate the Arab community recognized landmarks.
مذكرة ماستر تاريخ تخصص تاريخ حديث ومعاصر
Keywords: الدور الاجتماعي - الزوايا في وادي سوف - الأسرية - الاستعمار - تقاليد - الصّوفية - التّكافل - السّياسة .; Rôle social - Zawaya à Wadi Suf - Famille - Colonialisme - Traditions - Soufisme - Takaful - Politique.; Social role - Zawaya to Wadi Suf - Family - Colonialism - Traditions - Sufism - Takaful - Politics.